Plan de negocios para la apertura de una empresa organizadora de eventos y banquetes en el municipio de Quimbaya (2013)
In principle, readers will find the Methodological Design which discusses in detail the variables that influence the implementation of the proposed project, also the study population with optimal for economic activity of the company is determined characteristics, which is represented by a population of strata 2, 3, 4, 5 corresponding to 19,419 inhabitants in the municipality of Quimbaya which form part of the list provided by DANE after the census in 2005. To perform the market study took into account the competition interviews because they do not have a historical source or statistical studies of service events and banquets that allow project the amount of demand information in order to analyze the performance of this sector, and the service to be provided , its characteristics and use is clearly described. The Technical Study project duration, the required adaptation and equipment needs with your description, sale price and installation requirements and assembly is analyzed. Finally lease the premises where the work is estimated company. In the Administrative and Legal Study the company showing the steps legally required to do so, the legal restrictions on the payment of operating labor, administrative and outsourcing work in compliance with the Act constitutes. The Financial Studio, the main indicators of the project, the net present value (VPN) of $ 66,226,025, the Internal Rate of Return (TIR) of 32.68 % was found. With the determination of the above data is determined that the draft Business Plan for Starting a Business Organizing Events and Banquets in the municipality of Quimbaya, is feasible and profitable for its investors.